2014
DOI: 10.1377/hlthaff.2013.1300
|View full text |Cite
|
Sign up to set email alerts
|

Attention To Surgeons And Surgical Care Is Largely Missing From Early Medicare Accountable Care Organizations

Abstract: The Affordable Care Act supports the growth of accountable care organizations (ACOs) as a potentially powerful model for health care delivery and payment. The model focuses on primary care. However, surgeons and other specialists have a large role to play in caring for ACOs' patients. No studies have yet investigated the role of surgical care in the ACO model. Using case studies and a survey, we examined the early experience of fifty-nine Medicare-approved ACOs in providing surgical care. We found that ACOs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 8 publications
1
73
1
2
Order By: Relevance
“…While a handful of studies have examined the involvement of particular types of providers in ACOs (e.g. hospitals or community health centers) and associated issues of partnering with those organizations, 14 these studies cannot provide broader insight into the phenomenon of providers partnering under ACO contracts. In this paper, we address this gap in the literature by using mixed methods analysis (survey data, performance data, and semi-structured interviews) to describe the landscape of new partnerships between health care provider organizations associated with ACOs.…”
Section: Introductionmentioning
confidence: 99%
“…While a handful of studies have examined the involvement of particular types of providers in ACOs (e.g. hospitals or community health centers) and associated issues of partnering with those organizations, 14 these studies cannot provide broader insight into the phenomenon of providers partnering under ACO contracts. In this paper, we address this gap in the literature by using mixed methods analysis (survey data, performance data, and semi-structured interviews) to describe the landscape of new partnerships between health care provider organizations associated with ACOs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite suggestions that management of specialist referrals may be an important path to savings, 18,42 engagement with specialists has been limited. 43 Significant barriers exist in that the majority of specialty care is provided by physicians that are not part of the ACO. 44 For specialists participating in ACOs, revenue generated through the ACO typically accounts for a small percentage of total revenue, 45 potentially limiting their desire to develop innovative models of care financed through possible shared savings.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Dupree et al (2014) found that care coordination is seen as critical, with 86% of their survey respondents emphasizing the importance of avoiding wasted at LAURENTIAN UNIV LIBRARY on June 4, 2016 mcr.sagepub.com Downloaded from resources due to poor care coordination. Leaders of ACOs are also charged with creating a context and transmitting the incentives to ensure that the combined organization diligently pursues cost reduction, quality improvement, and population health.…”
Section: Practice Reliability-enhancing Leadershipmentioning
confidence: 99%